THE IMPORTANCE OF ISOOKTAN NUMBER IN GASOLINE - Norulov Uchqun Munavvorovich; Turdiyev Zarif Ziyodulla o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the importance of the number of isooctanes in gasoline composition. Determining the isooctane number, increasing the isooctane number.